2019
DOI: 10.3390/land8060089
|View full text |Cite
|
Sign up to set email alerts
|

The Slow Displacement of Smallholder Farming Families: Land, Hunger, and Labor Migration in Nicaragua and Guatemala

Abstract: Smallholders worldwide continue to experience processes of displacement from their lands under neoliberal political-economic governance. This displacement is often experienced as "slow", driven by decades of agricultural policies and land governance regimes that favor input-intensive agricultural and natural resource extraction and export projects at the expense of traditional agrarian practices, markets, and producers. Smallholders struggle to remain viable in the face of these forces, yet they often experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 17 publications
0
31
0
Order By: Relevance
“…On the contrary, our analysis confirmed that the strategies of agrarian neoliberalism in Chile continue unabated, disregarding the various studies showing the negative impacts and the deepening of inequalities in the rural regions. In particular, the loss of peasant livelihoods is reinforced by this type of agribusiness strategy, leading to a process of proletarianization with rural workers and small farmers conspicuously migrating to the city (a mass movement of people that in other Latin American countries has been called "slow displacement", [79]).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, our analysis confirmed that the strategies of agrarian neoliberalism in Chile continue unabated, disregarding the various studies showing the negative impacts and the deepening of inequalities in the rural regions. In particular, the loss of peasant livelihoods is reinforced by this type of agribusiness strategy, leading to a process of proletarianization with rural workers and small farmers conspicuously migrating to the city (a mass movement of people that in other Latin American countries has been called "slow displacement", [79]).…”
Section: Discussionmentioning
confidence: 99%
“…While the 1996 Peace Accords formally ended the conflict, enduring structural challenges and inequalities ensured the continuation of out-migration flows [64]. New postconflict neoliberal reforms favored expanded agrarian extractivism and other mining and energy "megaprojects" to the detriment of smallholder production, land access, and labor opportunities [4,17,60,110]. Today, many smallholders live under a condition of "slow displacement," in which prolonged neoliberal political-economic governance "[provokes] a kind of displacement from the land that [unfolds] slowly over years" [17] (p. 2).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, while scholars widely recognize that migration outcomes are heterogenous [28], analysis of differentiation has generally centered on comparative work between migrant and non-migrant households. Recent research by Carte et al [17] observes uneven socioeconomic outcomes among migrant cohorts, yet between groups engaged in distinct migration and political-economic processes from different migrant-sending countries.…”
Section: Towards Enforcement Landscapesmentioning
confidence: 99%
“…Signals of such long-term transformations run across all articles. The theme is perhaps most poignantly expressed in Carte et al's title "The slow displacement of smallholder farming families: land, hunger, and labor migration in Nicaragua and Guatemala" [30] (in this special issue). In both countries the formal end of civil wars brought a new era of neoliberal reforms of the rural economy to the advantage of intensive agricultural and natural resource extraction, often disadvantaging traditional agrarian practices and leading to waves of emigration in both countries.…”
Section: Transformationmentioning
confidence: 99%
“…An example may serve here to illustrate how intricate these long-term processes at the nexus of land use, income, and migration are. When cattle ranchers in Caballo Blanco, one of the study sites in Guatemala, started renting out their land for sugar cane production, less land was available to rent out or lend to community members for farming, especially at a rental price low enough for poor farmers, in turn leading to less agricultural production and hunger, which then triggered labor migration in order to be able to pay for the higher prices to rent land, which in turn increased the land rental prices even further leading non-migrant families (families who do not have a member who earns income elsewhere from labor migration) to become excluded from access to land; this in turn led more community members to migrate in order to send back at least the "money for some beans" [30] (p. 8). Migration is therefore both evidence of displacement but also a strategy for families to prolong their hold on the land as farmers.…”
Section: Transformationmentioning
confidence: 99%